Physical activity among Polish and English residents of nursing homes - Walewska, Elżbieta; Gołda, Agnieszka; Ścisło, Lucyna; Szczepanik, Antoni; Czupryna, Antoni (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Physical activity is one of the indicators of a healthy lifestyle. Physical activity after the age of 65 gives the ability to maintain physical capacity at a much higher level than people who live inactive lifestyle. Aim. The aim of this study was to assess the physical activity of older people living in Polish and English nursing homes. Material and methods. The study was conducted in February and March 2013. The research material consisted of 59 people. 29 respondents are residents in Chislehurst and 30 respondents are residents in Krakow. The research method was a diagnostic survey and the research tool was a questionnaire of own authorship.CDS and Barthel scale were used also. Results and Conclusions. The vast majority of respondents assessed their lifestyle which led in the past as active. In both groups, the most common response to the current fitness was moderate fitness. 76.3% of the respondents received Low levels depending on the care by CDS scale and the vast majority of people — 61 % was placed in Group I in accordance with the Barthel scale. It can be concluded that in the group of English respondents, lifestyle, fitness assessment were significantly associated with the results of the CDS scale and Barthel scale. The more active lifestyle in the past and higher subjective evaluation of the efficiency of the English residents, the favorable results of the CDS scale and Bartel scale. In the group of Polish residents such a relationship is not found. Nursing Topics 2014; 22 (4): 511–516